PENGALAMAN AKSEPTOR KB DALAM MEMAHAMI PERUBAHAN TUBUH SETELAH PENGGUNAAN KB SUNTIK 3 BULAN DI PUSKESMAS MULTIWAHANA - Faradiba, Selly (STIKES Abdurahman. Pusat Informasi dan Manajemen, 2026)
Three month injectable contraception is one of the most commonly used family planning methods among women of reproductive age. However, its use is often accompanied by bodily changes that may influence health behavior and decision making. This study aimed to explore the ecperiences of injectable contraceptive users in understanding bodily changes after the use of three month injectable contraception at Multiwahana Primary Health Center. This study employed a qualitative design with a descriptive phenomenological approach. Data were collected through in depth interviews with purposively selected users of three month injectable contraception. The number of participant was determined by data saturation. Data were analyzed using thematic analysis to identify key themes based on participants experiences. The finding revealed four main themes: initial awareness of bodily changes, confusion in interpreting bodily changes, strategies to respond to bodily changes, and health autonomy in contraceptive decision making. Although participants were aware of bodily changes, limited body literacy contributed of uncertainty bodily changes played an important role in strengthening health autonomy among contraceptive users. This study concludes that body literacy and heath autonomy are essential components of family planning health promotion.